Flight Period of Phαenops knoteki and Acαnthocinus reticulαtus - Markalas, S. (ENTOMOLOGIA HELLENICA, 1992)
The flight period of Phaenops knoteki (Coleoptera: Buprestidae) was extended front the end of May until the middle of August and Chat one of Acanthocinus reticulatus (Coleoptera, Cerambycidae) front middle of June until middle of September.